2014
DOI: 10.1556/aalim.2013.0007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing acylation and enzymatic hydrolysis on functional properties of bambara bean (Vigna subterranea) protein concentrate

Abstract: Bambara bean protein concentrate was acylated and partially hydrolysed with pancreatin in order to improve its functional properties. Increasing acetylation and succinylation (from 0.0 to 1.0 g anhydride/g concentrate) modified lysine at similar rate. Acylation markedly improved protein solubility and water solubility index at neutral pH, which reached to 92 and 94%, respectively. Acetylation showed greater effect on emulsifying activity, which was maximum at 0.5 g anhydride/g concentrate, and emulsifying stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The protein solutions were then centrifuged at 6,000× g for 20 min (Mune Mune et al . ). Protein concentration in each supernatant was determined by the Lowry method (Lowry et al .…”
Section: Methodsmentioning
confidence: 97%
“…The protein solutions were then centrifuged at 6,000× g for 20 min (Mune Mune et al . ). Protein concentration in each supernatant was determined by the Lowry method (Lowry et al .…”
Section: Methodsmentioning
confidence: 97%
“…Generally, solubility, surface hydrophobicity and molecular flexibility influenced the emulsifying behavior of globular proteins. Surface hydrophobicity was probably determinant for EA of cowpea and Bambara bean protein concentrates, since there was a positive correlation (r= 0.80; p< 0.00) between these two variables.Panyam & Kilara (24) and Mune Mune et al(25) reported that increase in surface hydrophobicity facilitated adsorption of proteins at the oil-water interface, then reduced the surface tension and increased emulsifying properties. In addition, the partial unfolding of protein molecules could increase their molecular flexibility, which facilitated their rearrangement at the oil-water interface to form an elastic layer around the fat droplets and then retarded coalescence.…”
mentioning
confidence: 99%
“…Previous studies showed that solubility of BBPC followed a U‐shaped trend at different pH levels, with the lowest solubility around pH 4.5 (Mune Mune et al . ). Nitrogen solubility of BPH was then followed at neutral and isoelectric pH and the results are presented in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In a previous work, we reported that functional properties of BBPC could be effectively modified by enzymatic hydrolysis using pancreatin (Mune Mune et al . ).…”
Section: Introductionmentioning
confidence: 97%